Process-Based Species Pools Reveal the Hidden Signature of Biotic Interactions Amid the Influence of Temperature Filtering (2016)
ABSTRACT: A persistent challenge in ecology is to tease apart the in-fluence of multiple processes acting simultaneously and interactingin complex ways to shape the structure of species assemblages. Weimplement a heuristic approach that relies on explicitly defining spe-cies pools and permits assessment of the relative influence of the mainprocesses thought to shape assemblage structure: environmentalfil-tering, dispersal limitations, and biotic interactions. We illustrate ourapproach using data on the assemblage composition and geographicdistribution of hummingbirds, a comprehensive phylogeny and mor-phological traits. The implementation of several process-based speciespool definitions in null models suggests that temperature—but not pre-cipitation or dispersal limitation—acts as the main regionalfilter of as-semblage structure. Incorporating this environmentalfilter directly intothe definition of assemblage-specific species pools revealed an other-wise hidden pattern of phylogenetic evenness, indicating that biotic in-teractions might further influence hummingbird assemblage structure.Such hidden patterns of assemblage structure call for a reexaminationof a multitude of phylogenetic- and trait-based studies that did not ex-plicitly consider potentially important processes in their definition ofthe species pool. Our heuristic approach provides a transparent wayto explore patterns and refine interpretations of the underlying causesof assemblage structure.